Retelling and rewriting a sad refrain (Laguna during the Japanese occupation) - Gotiangco, Gil G. (2007)
Local narratives and interviews with Lagunenses who lived in the province from 1941 to 1946 offer revealing new insights on the Japanese occupation in the Philippines. While the general consensus is a fervent hope that it will never happen again, information provided by both civilians and guerrillas suggests a kinder and ambivalent assessment of the social milieu from 1942 to the early months of 1944. Psychologically, this may be interpreted as a sober reflection of the wartime years, the informants having been detached from the aforementioned period for several decades now. The guerrillas, and particularly the civilians, noted a routinary life from 1942 to the first few months of 1944. Accordingly, distinctions have to be made among towns where Japanese military presence was strong and where it was minimally felt. Distinctions need also be made between the victims of the atrocities and the Japanese imperial forces involved. Interestingly, even the assessment of the MAKAPILI is equally ambivalent. Hated during the wartime years, the group is characterized in multi-faceted hues. The guerrilla campaign in Laguna is another vital feature of the Japanese occupation. Unlike most anti-Japanese resistance campaigns in the country, four groups operated independent of each other. The HUKBALAHAP, in particular, is worthy of special citation. How all these guerrilla groups fought and achieved modest success against the enemies is a tribute to military ingenuity and sympathy to a noble national cause. The narratives on the Japanese occupation in Laguna are more than a portrayal of the conquerors and the conquered. Both the resistance movement and the resultant social conditions speak vividly of the Filipino value system, humor, and resiliency in times of conflict and non-normative situations. These may explicably shed some light on post-war Laguna social milieu and political growth.